2022
DOI: 10.3390/diagnostics12112801
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Follow-Up Study of Patients with Papillary Thyroid Carcinoma Associated or Not with Graves’ Disease

Abstract: Whether papillary carcinoma (PC) behavior is more aggressive in Graves’ disease (GD) patients than PC cases without GD is controversial. We retrospectively enrolled 33 thyroidectomized PC/GD patients during long-term follow-up, 23/33 without risk factors at surgery, and 18/33 microcarcinomas; 312 PC euthyroid-matched patients without risk factors served as controls. A total of 14/33 (42.4%) PC/GD patients, 4 with and 10 without risk factors at diagnosis, 6 with microcarcinoma, underwent metastases during follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…The identification of metastases during follow-up is typically achieved through the use of traditional and highly sophisticated diagnostic imaging procedures, and in all patients, 131 I SPECT/CT has been included with high performance, confirming the reliable results of this procedure reported in the literature [42][43][44][45] also in patients with PC associated to thyroid autoimmune diseases [46,47].…”
Section: Discussionsupporting
confidence: 62%
“…The identification of metastases during follow-up is typically achieved through the use of traditional and highly sophisticated diagnostic imaging procedures, and in all patients, 131 I SPECT/CT has been included with high performance, confirming the reliable results of this procedure reported in the literature [42][43][44][45] also in patients with PC associated to thyroid autoimmune diseases [46,47].…”
Section: Discussionsupporting
confidence: 62%
“…However, it is a matter of controversy whether the behavior of the carcinomas is more aggressive when the two diseases are associated with thyroid cancer. It has been observed that the appearance of metastatic lesions during follow-up is more frequent in patients with PC/GD [34][35][36][37] and PC/HT [21,22,30,31] than in PC patients without these autoimmune diseases. However, other studies have observed no difference in the outcome in the patients with or without GD and HT [15,38,39], while others have suggested that the two diseases may be factors of a more favorable disease course [3,8,[10][11][12][13]20,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Marongju et al. revealed a higher degree of aggressiveness in some patients with microcarcinoma and GD compared to controls, even when tumor characteristics were favorable, which conflicts with other studies ( 45 ). The presence of both thyroid cancer and GD is a surgical indication, regardless of the size of the cancer.…”
Section: Discussionmentioning
confidence: 74%
“…In a study by Hales et al., the average size of thyroid cancer in patients with GD was 0.91 cm, which was significantly smaller than the average size in the euthyroid group (0.91 vs. 2.33 cm) ( 44 ). However, previous studies demonstrated a more aggressive thyroid cancer phenotype in patients with GD ( 9 , 45 ). In addition, Marongju et al.…”
Section: Discussionmentioning
confidence: 86%